THE IMPLEMENTATION OF THE BALANCE THEORY BASED ON JUSTICE VALUES IN THE NOTARY’S POSITION - Bachrudin, Bachrudin (Lambung Mangkurat Law Journal, 2019)
The theory of “Value-Based Equilibrium Balance”, is a legal theory built by the author in this paper. This theory constructs the importance of providing legal protection for notaries by balancing between the fulfillment of the basic rights of notaries as holders of rights with humans, and the basic rights of individual notaries as citizens by taking into account the basic values ​​of justice. This type of research is doctrinal legal research or normative in the realm of legal philosophy. The construction of this legal theory is motivated by the existence of competition in the notary office’s practice of unhealthy competition. Unfair competition as mentioned previously denies the nature of the position of a notary, influences the perfection of the notary in carrying out his position and makes the entrance for legal interests ensnare the notary as the holder of office. Assume other positions related to decisions or invitations from the government or government or other institutions related to the context of similarity or conformity. This theory is useful to bring the agenda of changes to structural structures that are unfair, specifically in the context of notary ownership and general in the national life.